Modeling of structures subjected to wind generated waves - Plate, Erich J., author; Nath, John H., author; Colorado State University, publisher (Colorado State University. Libraries, 1968)
The difficulties inherent in the direct determination of loads on off-shore structures which are exposed simultaneously to wind and waves make it desirable to model each situation in the laboratory. It is shown here that scaling of the loads and the waves is possible by using waves which are generated by blowing air over the surface of a laboratory channel, and by choosing a model material with an appropriate modulus of elasticity. Wind-generated waves such as those measured in the wind water tunnel of Colorado State University have a dimension less spectrum (Hidy and Plate (1965)) that is identical in shape to that found off the coast of Florida under hurricane conditions (Collins (1966)). Furthermore, it has been shown that hydro-elastic modeling is quite feasible (LeMehaute (1966)). These two results are combined to give modeling criteria for off-shore structures if direct wind forces are disregarded. Some consideration is also given to dynamic wind load modeling and to the question whether simultaneous modeling of both the wave and the wind forces is possible in a laboratory. In principle, this appears feasible, but for sufficiently large scale models, fetch lengths may be required which are larger than typical laboratory channels.
CER67-68EJP-JN68.
Keywords: Offshore structures -- Aerodynamics